The Creativity of Teachers Using Online Learning Media in Pandemic Covid-19 - Nuraini, Nuraini; Suhari, Suhari; Awalia, Rubi; Herwani, Herwani; Ubabuddin, Ubabuddin (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
Creativity is the potential of every individual that can be studied, processed, explored and developed for the better, not an innate talent and trait born in a person. In the implementation of learning, Creativity has an essential role in creating more active, fun, exciting learning and facilitates learning. Teacher creativity is the ability to find thoughts about ideas and ideas in solving a problem related to educational science. Creative teachers will continue to develop exciting learning to improve quality, improve materials, use methods, use media and manage classrooms. Especially during the current COVID-19 pandemic, a teacher is required to create exciting and fun learning. The Covid-19 pandemic that has occurred throughout the world, including Indonesia, involves implementing distance learning as instructed by the Ministry of Education and Culture to continue learning during this COVID-19 outbreak. Therefore, teachers at all levels of education must make new learning plans related to distance learning. Likewise, the teaching carried out at SMP Negeri 4 Subah, an area in the red zone of the spread of the COVID-19 outbreak, requires learning to be carried out online. This research was conducted at SMP Negeri 4 Subah with a qualitative approach or descriptive field research. The results show that teachers at SMP Negeri 4 Subah are ready to carry out online learning by utilizing media or applications that can support online learning to keep it exciting and fun, including using WhatsApp, Google Classroom, Google Form, Zoom Meeting, Email and other applications on when delivering subject matter, giving assignments and carrying out tests.